Utilization of gypsum from construction and demolition waste in Portland cement mortar - Antunes, M. L.P. [UNESP]; Botignon de Sá, A. [UNESP]; Oliveira, P. S. [UNESP]; Rangel, E. C. [UNESP] (FapUNIFESP (SciELO), 2019)
Civil construction generates the largest amount of construction and demolition waste (CDW), most of which is not reused and is discarded as inert waste in landfills. The purpose of this study was to evaluate the feasibility of reusing gypsum recovered from CDW in the preparation of mortar. This material was examined to determine its specific mass, morphology, elemental composition and particle size distribution. Test specimens were prepared with a mix design of 1:3 (cement:sand), with the gypsum waste substituting part of sand in proportions of 0, 10, 20 and 30% (in volume). The consistency of the fresh mortar was evaluated: the specimens were tested to determine their flexural and compressive strength, apparent density, water absorption, voids index, and specific mass. After 28 days, the mechanical strength of the specimens exceeded the limits specified by NBR 13281 standard, indicating that up to 30% of ground gypsum waste can be included in a mortar.
Keywords: Construction and demolition waste; Gypsum; Mortar; Portland cement